2021
DOI: 10.3390/su132011234
|View full text |Cite
|
Sign up to set email alerts
|

Controversy over the Use of “Shade Covers” to Avoid Water Evaporation in Water Reservoirs

Abstract: Water scarcity and sustainability are main current concerns affecting billions of people worldwide. Apart from policies designed to guarantee water supply, technologies and procedures have been developed to optimize the uses of water and water recycling as well as to minimize water scarcity. Among these technologies, those based on the use of bioinspired fibres, membranes, nanomaterials, liquid-liquid extraction methods using ionic liquids or approaches involving plants or microbes have been successfully carri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 51 publications
0
1
0
Order By: Relevance
“…R5-No update of water management instructions. R6-Possible negative impact on the morphology of the watercourse and the region downstream of the dam cross-section C2.2-Climate change impacts [53][54][55][56][57][58][59][60] The analyses concern 2 very large and 6 large reservoirs in Asia, 4 large reservoirs in Europe and a large reservoir system in South America. In addition, in [56] the reservoir capacity was a variable value, and in [60] a review based on a large dataset was performed.…”
Section: Retention Capacity Managementmentioning
confidence: 99%
See 3 more Smart Citations
“…R5-No update of water management instructions. R6-Possible negative impact on the morphology of the watercourse and the region downstream of the dam cross-section C2.2-Climate change impacts [53][54][55][56][57][58][59][60] The analyses concern 2 very large and 6 large reservoirs in Asia, 4 large reservoirs in Europe and a large reservoir system in South America. In addition, in [56] the reservoir capacity was a variable value, and in [60] a review based on a large dataset was performed.…”
Section: Retention Capacity Managementmentioning
confidence: 99%
“…The development of new technologies to technically reduce evaporation from storage tanks is also noticeable. However, studies have indicated that shade covers are not universally and widely applicable due to the high energy and water consumption in the production process, which translates into a high cost of implementing such a solution [60].…”
Section: C23-sediment Accumulation [61-68]mentioning
confidence: 99%
See 2 more Smart Citations
“…Modular floating covers were first designed to prevent water bird access to water storages close to airport runways (“bird balls,” Martinez‐Espinosa, 2021). Some municipal water managers adopted the strategy to reduce evaporative loss, which in the case of Los Angeles in the USA involved the release of 96 million 100 mm in diameter, high‐density polyethylene balls over the 175 acre water surface of the reservoir (Kavanaugh, 2016).…”
Section: Mode Of Action Environmental Impact and Performance Of Float...mentioning
confidence: 99%